THE INFLUENCE OF EDUCATION USING MODIFICATION MODULE ON KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF PREGNANCY CARE IN KENDARI, INDONESIA - Kartini Kartini; Muh Syafar; Arsunan A. Arsin; Burhanuddin Bahar; Fitriyanti Fitriyanti; Farming Farming (Public Health of Indonesia)
Background: Prenatal care is one way to prevent complications of pregnancy, and educational approach is the best approach to improve the knowledge of mothers about prenatal care.